Matei Vișniec, l’homme qui voulait être un oiseau… - Mirella Patureau (Recherches, 2011)
In the uncertain space of contemporary theater, at the borderline of failures and successive disappointments we have to situate the plays of a writer as Matei Vișniec, born in Romania and living in France since 1984, a writer who made the transition between two types of dramaturgy: from Aesopian language and the strategies of cunning, to create finally a theater linked to existential and poetical reflexion, without leaving the ground of political implications.